Preparation of Pt/C Catalyst by Coaxial Arc Plasma Deposition for Polymer Electrolyte Membrane Fuel Cells. (1st January 2015) - Agawa, Yoshiaki; Kunimatsu, Masayuki; Ito, Takeshi; Kuwahara, Yasutaka; Yamashita, Hiromi
Abstract : A coaxial arc plasma deposition (CAPD) source was developed to generate metallic nanoparticles (NPs) with sizes from sub-nanometer to several nanometers. Pt NPs were deposited on a carbon support by CAPD for use as a polymer electrolyte membrane fuel cell (PEMFC) electrode catalyst. The principle of catalyst formation and the mechanism for control of the particle size by CAPD were investigated. Transmission electron microscopy observations were performed for Pt/C catalysts with various Pt contents. Single PEMFCs were fabricated using 1, 5, and 10 wt% Pt/C catalysts, of which the best cell performance was obtained with the 10 wt% Pt/C catalyst.